2020
DOI: 10.1038/s41598-020-76312-x
|View full text |Cite
|
Sign up to set email alerts
|

Extent and prognostic value of MGMT promotor methylation in glioma WHO grade II

Abstract: MGMT promotor methylation is associated with favourable outcome in high-grade glioma. In glioma WHO grade II, it is unclear whether the extent of MGMT promotor methylation and its prognostic role is independent from other molecular markers. We performed a retrospective analysis of 155 patients with glioma WHO grade II. First, all 155 patients were assigned to three molecular groups according to the 2016 WHO classification system: (1) oligodendroglioma, IDH-mutant and 1p19q co-deleted (n = 81); (2) astrocytoma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Other cut-off points which have been validated in studies by others range from a mean MGMT promotor methylation of 7% to 30% [22,23] which is lower than our calculated cut-off points. Of interest, mean number of methylated CpG sites in glioblastoma as well as IDHwt astrocytoma with pTERTmut were comparable to mean number of methylated CpG sites in a cohort of glioma WHO grade II recently described by our group [8], suggesting extent of MGMT promotor methylation to be independent of histopathological WHO grade and may rather depend on molecular markers. Technical cut-off values for the distinction of methylated versus unmethylated cases usually would be set at the nadir of the distribution.…”
Section: A B C D Esupporting
confidence: 76%
See 1 more Smart Citation
“…Other cut-off points which have been validated in studies by others range from a mean MGMT promotor methylation of 7% to 30% [22,23] which is lower than our calculated cut-off points. Of interest, mean number of methylated CpG sites in glioblastoma as well as IDHwt astrocytoma with pTERTmut were comparable to mean number of methylated CpG sites in a cohort of glioma WHO grade II recently described by our group [8], suggesting extent of MGMT promotor methylation to be independent of histopathological WHO grade and may rather depend on molecular markers. Technical cut-off values for the distinction of methylated versus unmethylated cases usually would be set at the nadir of the distribution.…”
Section: A B C D Esupporting
confidence: 76%
“…In the prospective CATNON trial (which compares radiotherapy with or without chemotherapy), a subgroup analysis of IDHwt astrocytoma with molecular features of glioblastoma demonstrated improved survival for tumors with MGMT promotor methylation (but surprisingly did not find evidence for beneficial effects of alkylating chemotherapy among methylated tumors) [ 7 ]. We recently reported on a large cohort of gliomas WHO grade II, and found that a higher number of methylated CpG sites within the MGMT promotor region also represents a positive prognostic factor for outcome in gliomas of lower grades [ 8 ]. Of note, a subgroup analysis of our cohort showed that the prognostic value of MGMT promotor methylation was only retained in IDHwt astrocytomas, but not in IDH-mutant glioma with or without 1p19q co-deletion.…”
Section: Introductionmentioning
confidence: 99%
“… 19 A larger number of methylated CpG sites has also shown to be associated with favorable outcome for low-grade gliomas. 15 Taken together, a possible proposal is that within lower-grade IDH mutant gliomas, comparing MGMT methylated vs. MGMT unmethylated tumors, the extent of methylation may be similar quantitatively, despite being qualitatively different in our testing methods. This hypothesis will require further confirmation.…”
Section: Discussionmentioning
confidence: 95%
“… 14 This is also consistent with a recent retrospective analysis of 155 patients with grade II glioma, showing that MGMT promoter methylation is only prognostic for IDH wildtype astrocytoma, but not for IDH mutant gliomas, regardless of the 1p19q co-deletion. 15 …”
Section: Discussionmentioning
confidence: 99%
“…A subset of the included patients has partly been reported in a previous study on molecular markers in low-grade glioma 15 .…”
Section: Methodsmentioning
confidence: 99%